SUSTAINABLE HR PRACTICES AND THEIR INFLUENCE ON CORPORATE SUCCESS - Aajaz Ahmad Hajam; Alphonsa S John; Jo’rayeva Hilola Orif Qizi; Shayzaqova Shaxnoza; Muyassar Raxmonova Abdufattohovna; Narziyeva Visola; Rakhmatullayeva Sogdiana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The evolving concept of sustainability in business has broadened to include not just environmental concerns but also social and economic aspects, impacting various organizational practices, particularly human resource management (HRM). This review examines Sustainable Human Resource Management (Sustainable HRM) and its influence on organizational performance by integrating sustainability into HR practices, aiming to achieve economic, social, and environmental benefits. Despite the recognized potential of Sustainable HRM to enhance employee satisfaction, environmental outcomes, and financial performance, empirical evidence remains fragmented. This review seeks to synthesize existing research, identifying patterns, discrepancies, and the impact of sustainable practices on organizational outcomes. By doing so, it aims to provide a comprehensive understanding and practical recommendations for integrating sustainability effectively into HR practices. Recent studies underscore the role of Sustainable HRM in boosting innovation, adaptability, and aligning organizational practices with global sustainability goals, thus enhancing overall corporate reputation and operational success.